ENVIRONMENTAL EDUCATION IN PRIMARY SCHOOLS: THEORETICAL FOUNDATIONS AND INNOVATIVE APPROACHES (The Journal of Interdisciplinary Human Studies, 2026)
This article provides an in-depth analysis of environmental education in primary schools, focusing on both theoretical frameworks and practical implementation. It explores innovative pedagogical approaches including project-based learning, STEAM integration, reflective practices, and digital technologies. The study emphasizes cognitive development, emotional engagement, and behavioral change models. Environmental education is considered a key factor in shaping responsible, environmentally conscious individuals capable of contributing to sustainable development.
Keywords: environmental education; primary school; sustainability; ecological awareness; STEAM; behavioral change; project-based learning; inquiry-based learning